2014
DOI: 10.1186/1687-4722-2014-6
|View full text |Cite
|
Sign up to set email alerts
|

Production and perception of velar stop (de)voicing in European Portuguese and Italian

Abstract: Speech production and speech perception studies were conducted to compare (de)voicing in the Romance languages European Portuguese (EP) and Italian. For the speech production part, velar stops in two positions and four vowel contexts were recorded. The voicing status for 10 consecutive landmarks during stop closure was computed. Results showed that during the complete stop closure voicing was always maintained for Italian, and that for EP, there was strong devoicing for all vowel contexts and positions. Both l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Apparently EP fits neither into the aspirated–unaspirated type of languages such as German or English, nor into the strictly voiced–voiceless type of languages such as Italian or Slavic languages. In the following, we present different possibilities for the EP voicing distinction, all from a perceptual point of view; however, follow-up perceptual experiments have to be conducted (see results for EP and Italian presented by Pape and Jesus (2014)) to verify the speculations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Apparently EP fits neither into the aspirated–unaspirated type of languages such as German or English, nor into the strictly voiced–voiceless type of languages such as Italian or Slavic languages. In the following, we present different possibilities for the EP voicing distinction, all from a perceptual point of view; however, follow-up perceptual experiments have to be conducted (see results for EP and Italian presented by Pape and Jesus (2014)) to verify the speculations.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the following questions could be raised, especially when seen in the light of cross-linguistic perceptual research: what are the cues that the perceptual system chooses to form a robust voicing distinction, and how is weighting among the available cues mediated? For vowel perception, it has been shown that the human perceptual system is not only able to perform certain weighting techniques between cues (i.e., to apply cue-trading ) in order to achieve a robust perceptual outcome, but, in addition, this weighting differs across different dialects and languages (Escudero, Benders, & Lipski, 2009; Morrison, 2005; Pape & Jesus, 2014). For the perception of obstruent voicing, this cue weighting is assumed to be highly language-dependent: while some languages merely rely on the strong cues like VOT, other languages may rely on voicing maintenance, closure duration or vowel duration instead.…”
Section: Introductionmentioning
confidence: 99%
“…Our fricative corpus was originally collected by the first author of this study for her dissertation research, which addresses the topic of secondary palatalization more generally (Spinu 2010). Due to the focus on secondary palatalization and the characteristics of its distribution in Romanian, there are important differences between our stimuli and those used in the majority of previous studies, such as the VC syllabic structure, as compared to CV (with exceptions such as Jesus and Shadle 2002, Pape and Jesus 2014, and Maniwa et al 2009, who also examined fricatives in a VCV context) and the inclusion of plain and palatalized fricative pairs, allowing us to compare these two types of segments directly. This is particularly noteworthy because, to our knowledge, no large-scale studies have attempted the classification of plain versus palatalized segments based on their acoustic properties.…”
Section: Current Studymentioning
confidence: 99%
“…This is justified by evidence from perception. For instance, Pape & Jesus (2014) demonstrate that a perceptual voicing threshold can be found as early as at the 20–25% mark of stop duration, and that listeners can reliably differentiate between voiced and voiceless intervocalic stops in which voicing is maintained for more than 50% of the duration of the sound. Similar results were found for other languages (Snoeren et al 2008, Mercier 2019).…”
mentioning
confidence: 99%